CORPORATE GOVERNANCE, CAPITAL INTENSITY DAN TRANSFER PRICING: DAMPAK TERHADAP TAX AVOIDANCE - Wulan Novita Sari (2022)
This study is a quantitative secondary data study aimed at analyzing the effect of Corporate Governance, Capital Intensity and Transfer Pricing on Tax Avoidance. The independent variable in this study is Corporate Governance which is proxied by the Independent Commissioner and the Audit Committee, Capital Intensity and Transfer Pricing, while the dependent variable is Tax Avoidance which is proxied by using Book Tax Difference (BTD). While the control variable in this study is Sales Growth. The sample used in this study, namely all sectors of manufacturing companies listed on the IDX for the period 2018-2020. The results of the test show that (1) the Independent Commissioner has a significant positive effect on Tax Avoidance, (2) the Audit Committee has a significant negative effect on Tax Avoidance. (3) Capital Intensity does not have a significant effect on Tax Avoidance, (4) Transfer Pricing does not have a significant effect on Tax Avoidance.